ANALISIS USAHATANI LENGKUAS (Alpinia galanga) DI KELURAHAN SUKA MULYA KECAMATAN SEMATANG BORANG KOTA PALEMBANG PROPINSI SUMATERA SELATAN - Sri Rahayu Endang Lestari (Jurnal AGRIBIS, 2022)
Analysis of Lengkuas Farming (Alpinia galanga (L) Sw) case study in Sukamulya Subdistrict Sematang District Borang Palembang City.  This study aims to find out how much income and profits galangal farming is implemented in Sukamulya Village District Sematang Borang Palembang City, This study was conducted from February to June 2018.Population in this research is farmer of lengkuas in Sukamulya Subdistrict of Sematang District Borang Palembang as many as 60 farmers. Sampling is using simple random sampling (Simple Random Sampling) of 30% of the total population of 18 farmers as a respondent lengkuas.  The calculated operational definitions are fixed costs including land lease fees and equipment depreciation. Variable costs include purchasing seeds, fertilizers, labor in the family. Production of galangal, receipts received by farmers per year, farmer's income and profit galangal farming in Sukamulya Village Sematang District Borang Palembang City. The results showed that the average production cost of sample farmers in Sukamulya village was Rp 49.393.594, -/Ha/Planting season. Receipt of farmers in Sukamulya Village Sukamulya District Borang Palembang City an average of Rp 77.385.000, -/Ha/Planting season. The average income of lengkuas farming in Sukamulya sub-district of Sematang Borang sub-district of Palembang is Rp. 27.991.406, -/Ha/Planting season. The result of analysis of farmer farming system in Sukamulya Village Subdistrict Sematang Borang City Palembang R/C is obtained at the farmer of example of galangal farming of 1.57 means that every Rp 1000, - the cost incurred by farmer, will get the acceptance of Rp 1,570,-. So the cultivated galvanized farming is profitable because R/C >1. Key words : Farming, Lengkuas, Cost and Marketing Flow